Human blood metabolites and lacunar stroke: A Mendelian randomization study. Issue 1 (January 2023) - Guo, Meng-Nan; Hao, Xiao-Yan; Tian, Jie; Wang, Yun-Chao; Li, Jia-Di; Fan, Yu; Shi, Jing-Jing; Ma, Dong-Rui; Li, Shuang-Jie; Zuo, Chun-Yan; Liang, Yuan-Yuan; Li, Meng-Jie; et al.
Background: Lacunar stroke accounts for a quarter of all strokes, but little is known about the underlying pathological mechanisms. Analysis of serum metabolites may allow better understanding of the underlying biological processes. Mendelian randomization (MR) can provide information on the causality of associations. Aims: To identify causal relationships between serum metabolites and lacunar stroke. Methods: We applied a two-sample MR analysis to evaluate relationships between 486 serum metabolites and lacunar stroke. The inverse-variance weighted (IVW) method was used to estimate the causal relationship of the exposure on the outcome, while sensitivity analyses were performed using MR-Egger, weighted median, and MR-PRESSO to eliminate the pleiotropy. We also performed a metabolic pathway analysis to identify potential metabolic pathways. Results: We identified 15 known (8 risk and 7 protective) and 14 unknown serum metabolites associated with lacunar stroke. Among the known risk metabolites, two were lipids (1-linoleoylglycerophosphoethanolamine and dihomo-linolenate (20:3n3 or n6)), five amino acids (kynurenine, isobutyrylcarnitine, aspartate, trans-4-hydroxyproline, and 3-methyl-2-oxovalerate), and one peptide (ADSGEGDFXAEGGGVR). The known protective metabolites included four lipids (4-androsten-3beta, 17beta-diol disulfate 1, 1-palmitoleoylglycerophosphocholine, adrenate (22:4n6), and glycodeoxycholate), one amino acid (methionine), and two exogenous metabolites (homostachydrine and 2-methoxyacetaminophen sulfate). Metabolic pathway analysis identified several pathways that might be involved in the disease. Conclusion: We identified eight risk and seven protective human serum metabolites associated with lacunar stroke. Isobutyrylcarnitine was positively associated with an increased risk of lacunar stroke. In addition, 3-methyl-2-oxovalerate and aspartate may be involved in the disease pathogenesis through metabolic pathways.